Congress, the press, and political accountability - Arnold, R. Douglas, 1950- (New York ; Princeton, New Jersey : Russell Sage Foundation : Princeton University Press, 2004)
"Congress, the Press, and Political Accountability is the first large-scale examination of how local media outlets cover members of the United States Congress. Using three samples of local newspapers from across the country, Arnold analyzes all coverage over a two-year period - every news story, editorial, opinion column, letter, and list." "The results show enormous variation in coverage. Some newspapers cover legislators frequently, thoroughly, and accessibly. Others - some of them famous for their national coverage - largely ignore local representatives. The analysis also confirms that only those incumbents or challengers in the most competitive races, and those who command huge sums of money, receive extensive coverage."--Jacket
Legislators, journalists, and citizens -- Explaining the volume of newspaper coverage -- How newspapers cover legislators -- Legislators as position takers -- Legislators and policy makers -- Legislators as candidates --How newspapers differ -- Effects of newspaper coverage on citizens -- The press and political accountability.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: United States. -- Congress -- Press coverage -- United States; United States. -- Congress; USA -- Congress; États-unis. -- Congress; USA / Kongress; Press and politics -- United States; États-Unis. Congress, dans la presse -- États-Unis.; Presse et politique -- États-Unis.; LANGUAGE ARTS & DISCIPLINES -- Journalism; Press and politics; Press coverage; United States; Berichterstattung; Presse; Nieuwsbladen; Berichtgeving; Volksvertegenwoordigers; Het Congres; Presse; Journalisme politique; Aspect politique; Responsabilité; États-Unis.; Electronic book